Impact of Gut Microbiota in Brain Ageing: Polyphenols as Beneficial Modulators - Fiorella Sarubbo; David Moranta; Silvia Tejada; Manuel Jiménez; Susana Esteban (MDPI AG, 2023)
Brain ageing is a complex physiological process that includes several mechanisms. It is characterized by neuronal/glial dysfunction, alterations in brain vasculature and barriers, and the decline in brain repair systems. These disorders are triggered by an increase in oxidative stress and a proinflammatory state, without adequate antioxidant and anti-inflammatory systems, as it occurs in young life stages. This state is known as inflammaging. Gut microbiota and the gut-brain axis (GBA) have been associated with brain function, in a bidirectional communication that can cause loss or gain of the brain's functionality. There are also intrinsic and extrinsic factors with the ability to modulate this connection. Among the extrinsic factors, the components of diet, principally natural components such as polyphenols, are the most reported. The beneficial effects of polyphenols in brain ageing have been described, mainly due to their antioxidants and anti-inflammatory properties, including the modulation of gut microbiota and the GBA. The aim of this review was, by following the canonical methodology for a state-of-the-art review, to compose the existing evidenced picture of the impact of the gut microbiota on ageing and their modulation by polyphenols as beneficial molecules against brain ageing.